Chaco ansilta new species from Mendoza province, western Argentina (Araneae: Nemesiidae) - Ferretti, Nelson Edgardo (2014)
new species of Chaco Tullgren, 1905 is described and illustrated from the Andean foothills of Mendoza province, western Argentina. This is the tenth species of the genus and the first record of Chaco in Mendoza. An updated key is presented for all Chaco species and a cladistic analysis was made based on a previously published morphological character matrix that now includes the newly described species.